2022
DOI: 10.3746/jkfn.2022.51.5.428
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physicochemical Characteristics, Functional Compounds, and Physiological Activities in Adzuki Bean Cultivars

Abstract: This study was undertaken to investigate the physicochemical characteristics, functional compounds, and physiological activities of adzuki bean cultivars. The crude lipid and protein contents showed a significant difference between AB cultivars, ranging from 0.30∼0.76% and 21.54∼24.09%, respectively. Starch and amylose contents were determined to range between 46.77∼51.51% and 15.67∼18.24%, respectively, and were relatively lower in 'Yeonduchae' than in other cultivars. Breakdown, which is an index of superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Zhang et al [19] reported that the total flavonoid content of peanut skin increased following ozone treatment. Recently, we reported that atmospheric pressure plasma treatment increases the total phenolic and flavonoid content in peanut shells [3]. In this study, it was postulated that the increase in Changes in the functional compound (total phenolic and flavonoid) content in peanut shells treated by an electron-beam in different states of the sample and dose levels are shown in Figure 2.…”
Section: Evaluation Of Extract Color and Functional Compound Content ...mentioning
confidence: 83%
See 2 more Smart Citations
“…Zhang et al [19] reported that the total flavonoid content of peanut skin increased following ozone treatment. Recently, we reported that atmospheric pressure plasma treatment increases the total phenolic and flavonoid content in peanut shells [3]. In this study, it was postulated that the increase in Changes in the functional compound (total phenolic and flavonoid) content in peanut shells treated by an electron-beam in different states of the sample and dose levels are shown in Figure 2.…”
Section: Evaluation Of Extract Color and Functional Compound Content ...mentioning
confidence: 83%
“…Zhang et al [19] reported that the total flavonoid content of peanut skin increased following ozone treatment. Recently, we reported that atmospheric pressure plasma treatment increases the total phenolic and flavonoid content in peanut shells [3]. In this study, it was postulated that the increase in the functional compound content in the solid treatment may be attributed to cell wall modification and/or decomposition of the chemical bonds of the polyphenolic compounds induced by electron-beam irradiation.…”
Section: Evaluation Of Extract Color and Functional Compound Content ...mentioning
confidence: 92%
See 1 more Smart Citation
“…Antioxidant activity is associated with antioxidant content, including phenolic compounds and flavonoids. Additionally, polyphenols, which are present in various grains, have beneficial biological effects, including antioxidant activity 27 . This result indicates that mixed grains, such as oats, sorghum, finger millet, adzuki bean, and proso millet, are rich sources of various polyphenols that possess an excellent antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro antioxidant free radical scavenging activity of the DI-blended was determined using 2,2′-azino-bis(3-ethylbenzothiazolin-6-sulfonic acid) (ABTS) according to the method described in our previous study with a slight modification 27 . Briefly, 10 µL of the extract was mixed with 200 µL of 7.4 mM ABTS solution, and the mixture was incubated for 60 min.…”
Section: Methodsmentioning
confidence: 99%